Handbook for ICT Projects for Rural Areas - AP Dr Fitri Suraya Mohamad, AP Dr Fitri; Jaya Laxshmi Meenatchisundaram, Jaya Laxshmi; Adam Francis, Adam; Hutchatai Chanlekha, Hutchatai Chanlekha; Dominic Solpico, Dominic Solpico; Gemalyn Dacillo Abrajano, Gemalyn Dacillo Abrajano; Kitso Kusin, Kitso Kusin; Hideyuki Iwata, Hideyuki Iwata; Hajime Koto, Hajime Koto; Hideki Yamamoto, Hideki Yamamoto; Masatoshi Mano, Masatoshi Mano (Universiti Malaysia Sarawak (UNIMAS), 2016)
This handbook identifies guidelines and fundamental requirements that can be of use to project managers and teams who are keen on initiating ICT projects in rural areas. Contents are based on the experiences by the authors when rolling out ICT projects in remote areas within Asia Pacific. The handbook is an accumulation of ideas and experiences from SHARE projects, an initiative driven by Telecommunication Technology Committee Japan (TTC) Japan, in which four countries, namely Malaysia, Indonesia, Thailand and the Philippines, have rolled out various technology-based projects in remote and rural locations. The book describes a narrative of guidelines, which are organised according to phases of development for a technology-enabled solution. The writing of the handbook takes into account the unique considerations for accommodating to local needs and competencies in remote and rural communities.